Differences in gastrointestinal hormones and appetite ratings between individuals with and without obesity—A systematic review and meta‐analysis. (23rd November 2022) - Aukan, Marthe Isaksen; Coutinho, Silvia; Pedersen, Sindre Andre; Simpson, Melanie Rae; Martins, Catia
Summary: Determining if gastrointestinal (GI) hormone response to food intake differs between individuals with, and without, obesity may improve our understanding of obesity pathophysiology. A systematic review and meta‐analysis of studies assessing the concentrations of GI hormones, as well as appetite ratings, following a test meal, in individuals with and without obesity was undertaken. Systematic searches were conducted in the databases MEDLINE, Embase, Cochrane Library, PsycINFO, Web of Science, and ClinicalTrials.gov . A total of 7514 unique articles were retrieved, 115 included in the systematic review, and 70 in the meta‐analysis. The meta‐analysis compared estimated standardized mean difference in GI hormones' concentration, as well as appetite ratings, between individuals with and without obesity. Basal and postprandial total ghrelin concentrations were lower in individuals with obesity compared with controls, and this was reflected by lower postprandial hunger ratings in the former. Individuals with obesity had a lower postprandial concentration of total peptide YY compared with controls, but no significant differences were found for glucagon‐like peptide 1, cholecystokinin, or other appetite ratings. A large methodological and statistical heterogeneity among studies was found. More comprehensive studies are needed to understand if the differences observed are a cause or a consequence of obesity.